Outcomes of pleural decortication in a tertiary care hospital of Telangana state - Kummari, Madhusudan; Malempati, Amaresh Rao; Palanki, Surya S. Gopal; Bomma, Kaladhar; Goutham, Chakravarthy (International Surgery Journal, 2020)
Background: The objective of the study was to study the clinical profile, incidence of postoperative complications in patients undergoing pleural decortication. Methods: The subjects for the study were selected from the cases admitted in a single unit of Department of Cardiothoracic Surgery, Nizam’s Institute of Medical Sciences, Hyderabad during the period of 2016 to 2018 and due ethics committee approval was taken. Collection of data is done from the database including admission record, ICU charts, discharge records and follow-up records. 50 patients underwent surgery. Outcomes and complications were analyzed for 3 years duration. Results: 50 patients were included in this study with different aetiologies that required pleural decortication. The average age of patients in our study was 34 years. Most patients in our study were male (80%) and had history of infection with tuberculosis (42%) and pyogenic (28%) infection. A few patients had history of trauma (12%). Most of the patients suffered from cough (88%), dyspnoea (74%), fever (82%) and haemoptysis (22%). The common postoperative complications we encountered were pleural air leak (37.5%) bleeding (25%) infection (25%) and recurrence (2%). Overall morbidity from pleural decortication was seen in 16 patients, and there was no mortality. Conclusions: The most common reason for pleural decortication is still empyema thoracis secondary to infection in the developing countries. Tuberculosis is still the most common cause leading to fibrothorax requiring pleural decortication followed closely by pyogenic lung infections and trauma.